The Correlation between Effective Communication and Patient Satisfaction in the Emergency Department - Abdul Aziz Hafifi; Suhari Suhari; Rizka Yunita (KHD Production, 2025)
Communication is a determinant of success in achieving goals. Every nurse must have skills in communicating with patients to build good relationships. This is very important to determine patient satisfaction and improve the quality of patient service. This research uses the cross-sectional study method. The population was 283 people, with 166 samples collected using the Slovin formula using an accidental sampling technique with two variables: effective communication and patient satisfaction. The data collection instrument in this research was a questionnaire (using a checklist). Then, the data was analyzed using the Spearman rank test. The results obtained were 155 people (93.37%) effective communication and 11 (6.62%) ineffective communication. One hundred sixty-two patients (97.53%) were satisfied, and four people were dissatisfied (2.47%), and the results were at a significant level p=0.000. A strong positive correlation was found between effective communication and patient satisfaction, meaning improved communication leads to higher patient satisfaction. Effective communication ensures that patients feel valued and comfortable, ultimately contributing to better healthcare experiences and outcomes.